Prediction of Femoral Strength Based on Bone Density and Biochemical Markers in Elderly Men With Type 2 Diabetes Mellitus - Jia, Shaowei; Gong, He; Zhang, Yingying; Liu, Hongmei; Cen, Haipeng; Zhang, Rui; Fan, Yubo (Frontiers in Bioengineering and Biotechnology, 2022)
Purpose: Effects of bone density, bone turnover and advanced glycation end products (AGEs) on femoral strength (FS) are still unclear in patients with type 2 diabetes mellitus (T2DM). This study aims to assess and predict femoral strength and its influencing factors in elderly men with T2DM. Methods: T2DM patients (n=10, mean age, 68 years) and age-matched controls (n=8, mean age, 62 years) were recruited. Femoral bone mineral density (BMD) and serum biochemical indices of all subjects were measured. FS was evaluated through finite element analysis based on quantitative computed tomography. Multiple linear regression was performed to obtain the best predictive models of FS and to analyze the ability of predictors of FS in both groups. Results: FS (p=0.034), HbA1c (p=0.000) and fasting blood glucose (p=0.000) levels of T2DM group were significantly higher than those of control group; however, the P1NP level (p=0.034) was significantly lower. FS was positively correlated with femoral neck T score (FNTS) (r=0.794, p<0.01; r=0.881, p<0.01) in both groups. FS was correlated with age (r=-0.750, p<0.05) and pentosidine (r=-0.673, p<0.05) in T2DM group. According to multiple linear regression, FNTS and P1NP both contributed to FS in two groups. P1NP significantly improved the prediction of FS in both groups, but significant effect of FNTS on predicting FS was only presented in control group. Furthermore, pentosidine, age and HbA1c all played significant roles in predicting FS of T2DM. Conclusion: Femoral strength was higher in elderly men with T2DM, which might be caused by higher BMD and lower bone turnover rate. Moreover, besides BMD and bone formation level, AGEs, blood glucose and age might significantly impact the prediction of femoral strength in T2DM.